The Sisters of Mercy in the Crimean War: Lessons for Catholic Health Care. (February 2017) - Paradis, Mary Raphael; Hart, Edith Mary; O'Brien, Mary Judith
In 1856, an appeal went out to nurses in both England and Ireland, and especially to religious nurses, to care for the troops fighting in the Crimean War. The Sisters of Mercy, founded in 1831 by Venerable Catherine McAuley, answered that call. This article describes the enormous challenges the Sisters faced in that mission, which was a test of their nursing skills, flexibility, organizational ability, and their spirit of mercy. The challenges they faced professionally and as religious Sisters, the manner in which they faced those challenges, and their spiritual lives as religious women shaped their ability to give comprehensive care. Some applications are made to the challenges which religious communities and organizations working in health care face in our country at this time. Summary: This article describes the challenges faced by a group of Sisters of Mercy from England and Ireland who volunteered to serve as nurses in the Crimean War from 1856 to 1858. Applications are made to challenges which are faced by religious communities and organizations in the current secular healthcare environment.